Effects of Different Processing Methods on Nutrient Digestibility in Broiler Chickens - Sabuna, Cytske; Deko, Maria Karolina; Koni, Theresia Nur Indah (Faculty of Animal Science, Universitas Brawijaya, 2025)
This research aimed to study the effects of different herb processing methods on the nutrient digestibility of broilers chickens. The herbs were processed via two methods: the boiling method and the water and steam distillation method. In this study, 135 broiler chickens were divided into 3 treatment groups: control (without herb processing), boiled, and water and steam distillation. The data obtained were analysed by one-way analysis of variance. The results revealed that the herbs produced via the boiling method and the herbs produced via the water and steam distillation methods presented increased organic matter digestibility and crude protein digestibility but decreased crude fibre digestibility in broilers compared with those produced without herbs. Thus, the herbs produced via the boiling method and the herbs produced via the water and steam distillation method can be recommended to farmers.